Legong Krincing Suara - Ni Kadek Intan Pramudita Dewi; I Wayan Sutirtha; I Putu Bagus Bang Sada Graha Saputra (Jurnal IGEL : Journal Of Dance, 2025)
Legong Krincing Suara The Legong Krincing Suara dance is a new Legong dance creation with Gongseng as the creative source of creation. The stylist tries to combine aspects of movement, music, make-up and fashion, namely Legong and Gongseng. The creation of the Legong Krincing Suara dance uses the Panca Sthiti Ngawi Sani creation method created by Prof. Dr. I Wayan Dibia, SST, MA. Which include: Ngawirasa, Ngawacak, Ngaplan, Ngawangun, and Ngebah. This dance is performed in a group using 6 female dancers with a dance structure, part 1 depicts the sound of gongseng like a "voice" that comes from all directions, part 2 describes the sound play produced by gongseng which is combined with legong movements that have been developed, and part 3 depicts small balls moving in the gongseng, giving rise to irregular or irregular sounds. The duration of this work is 10 minutes 33 seconds and uses Musical Instrument Digital Interface (MIDI) accompaniment using Legong gambelan combined with Gongseng Sound. Using general Legong dance make-up and clothing with some modifications to the fan and the addition of Gongseng anklets. Keywords : Legong Dance Krincing Suara, Gongseng, Legong.